2015
DOI: 10.5296/ijafr.v5i2.7782
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy Prediction for Non-Financial Firms of Pakistan

Abstract: In this study we use two models for the measuring of financial status of the non-financial firms which are listed in the Karachi Stock Exchange. The Non-financial companies represent the biggest slice at the Karachi Stock Exchange. The non-financial companies of Pakistan are the total population and sample size is 25 higher and 25 lower capital companies. The ISSN 2162-3082 2015 www.macrothink.org/ijafr 27 technique which used in this study was Convenience sampling technique and all 50 non-financial listed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Recently, Tinoco and Wilson (2013) tested the performance of the Altman (1968) Z-score model for UK firms and noticed a significant decrease in the prediction accuracy of the model than the original study. On the other hand, Roomi et al (2015) reported that the Z-score model is a good predictor for predicting financial distress of Pakistani firms. Moreover, Jaffari and Ghafoor (2017) found that the logit model is better than MDA, but the prediction accuracy of the models declines when applied to the Pakistani market.…”
Section: Comparative Positionmentioning
confidence: 99%
“…Recently, Tinoco and Wilson (2013) tested the performance of the Altman (1968) Z-score model for UK firms and noticed a significant decrease in the prediction accuracy of the model than the original study. On the other hand, Roomi et al (2015) reported that the Z-score model is a good predictor for predicting financial distress of Pakistani firms. Moreover, Jaffari and Ghafoor (2017) found that the logit model is better than MDA, but the prediction accuracy of the models declines when applied to the Pakistani market.…”
Section: Comparative Positionmentioning
confidence: 99%
“…The very first step is to find out the defaulted firms in Pakistan for the period of 2014-2015, as this period has been selected as this is the most recent financial data available for all listed companies. The total population of current research involves all the companies listed as non-financial in PSX (Abbas & Ahmad, 2011;Ahmed, 2016;Roomi et al, 2015)and also to identify the firms that has been bankrupt in PSX record. The analysis reports of PSX are obtained to determine the bankrupt companies' sample.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Therefore, we used Z-score (Altman 1968) and ZMI-score (Zmijewski 1984), two widely used measures of insolvency risk (Laeven and Levine 2009;Kanagaretnam et al 2011) to proxy a firm's bankruptcy risk. Researchers have found Altman's Z-score an effective and accurate tool to assess the financial distress of nonfinancial firms in Pakistan (Awais et al 2015;Hussain et al 2014;Roomi et al 2015). In the Altman (1968) model, low (high) values of the Z-score indicate that firm is at a higher (lower) level of risk.…”
Section: Dependent Variablementioning
confidence: 99%